Pengaruh Krim Ekstrak Clitoriaternatea terhadap Jumlah Neutrofil Kulit yang Dipapar Sinar Ultra Violet B - Purnamasari, Rina; Widiyanto, Bagas (Universitas Malahayati, 2023)
ABSTRACT Ultraviolet B radiation can cause photodamage to the skin. Clitoria ternatea is one of the natural ingredients that contains flavonoids which can use as anti-inflammatory due to UV B light exposure. This research uses a randomized post-test only control group design. The sample use 25 male wistar rats were divided into 5 groups, the normal control group, the negative control group which received UV B light exposure, the positive control group which received UV B light exposure and SPF 30 sunscreen, the P1 group which received UV B light exposure and extract cream. Clitoria ternate dose of 2.5%, group P2 received exposure to UV B light and Clitoria ternate extract cream dose of 5%. The number of neutrophils was observed by staining with hematoxylin eosin, under a light microscope with a magnification of 200x. Data were analyzed by Kruskall Wallis with the Mann Whitney Post Hoc Test. The highest average number of neutrophils was found in the negative control group (1.24 ± 1.69), while the lowest average value shown by the normal control group (0 ± 0). TheKruskall Wallis test ha p<0.05, which means there was a significant difference between groups. The results of the Mann-Whitney Post Hoc Test showed a value of p <0.05 between normal control group with negative controls, P1 and P2; negative control with positive control, P1 and P2. While the value of P> 0.05, which means there is no significant difference between the two groups shown in the normal control group with positive control, positive control with P1 and P2; group P1 with P2. From the results of this study can be concluded that Clitoriaternatea extract cream has an effect on the number of neutrophils exposed to ultra violet B rays. Keywords: Anti-Inflammatory, Clitoria Ternatea, Neutrophils, Ultra Violet ABSTRAK Radiasi sinar ultra violet (UV) B memiliki dampak photodamage pada kulit. Clitoria ternatea salah satu bahan alam yang memiliki kandungan flavonoid yang dapat berperan sebagai antiinflamasi akibat paparan sinar UV B. Penelitian ini menggunakan randomized post-test only control grup design. Sampel sebanyak 25 ekor tikus jantan galur wistar yang dibagai dalam 5 kelompok yaitu yaitu kelompok kontrol normal, kelompok kontrol negatif yang mendapat paparan Sinar UV B, kelompok kontrol positif mendapat paparan Sinar UV B dan tabir surya SPF 30, kelompok P1 mendapat paparan Sinar UV dan krim ekstrak Clitoria ternate dosis 2,5%, kelompok P2 mendapat paparan Sinar UV B dan krim ekstrak Clitoria ternate dosis 5%. Jumlah neutrofil diamati dengan pengecatan hematoksilin eosin, dibawah mikroskop cahaya perbesaran 200x. Data dianalisis dengan Kruskall Wallis dengan Post Hoc Test Mann Whitney. Rata-rata jumlah neutrofil tertinggi terdapat pada kelompok kontrol negatif (1.24 ± 1.69), sedangkan nilai rerata terendah ditunjukkan oleh kelompok kontrol normal (0 ± 0). Hasil uji Kruskall Wallis didapatkan nilai p<0.05 yang berarti terdapat perbedaan secara signifikan antar kelompok. Hasil uji Post Hoc Test Mann-Whitney didapatkan nilai P<0.05 pada kelompok kontrol normal dengan kontrol negatif, P1 dan P2; kontrol negatif dengan kontrol positif, P1 dan P2. Sedangkan nilai P>0.05 yang berarti tidak terdapat perbedaan signifkan antar dua kelompok ditunjukkan pada kelompok kontrol normal dengan kontrol positif, kontrol positif dengan P1 dan P2; kelompok P1 dengan P2. Dari hasil penelitian dapat disimpulkan bahwa krim ekstrak Clitoriaternatea berpengaruh terhadap jumlah neutrofil yang dipapar sinar ultra violet B. Kata Kunci: Antiinflamasi, Clitoria Ternatea, Neutrofil, Ultra Violet